Evaluation of cerebral cortex activation during balance tasks using fNIRS: a systematic review - Sathe, Abhinav; Shenoy, Shweta; Sathe, Prachi Khandekar (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Functional near-infrared spectroscopy (fNIRS) is used as a neuroimaging tool for the study of different areas of the brain involved in motor control through the measurement of changes in brain hemodynamics. Its wireless usage and portability has made it suitable for investigating the cortical control of postural balance under static and dynamic testing conditions. Aim of Study. The aim of this systematic review is to evaluate studies on cortical activation while performing static and dynamic balance tasks using fNIRS as a tool and emphasizing the location of brain areas activated. Material and Methods. The search was performed following the PRISMA guidelines. Relevant keywords were used for the search through Google Scholar, PubMed, Science Direct, Taylor and Francis, and Scopus. The methodological quality of included studies was assessed using the Downs and Black checklist. Ten studies met the inclusion criteria. Results. The included studies were found to be of good methodological quality. The results in this review showed that the dorsolateral prefrontal cortex, sensory motor area and superior temporal gyrus are activated predominantly during static and dynamic balance tasks. Conclusions. The recent findings reflect a whole new scope of analysis involving multitasking during complex motor activities. The fNIRS technique is an adjunct to assess static and dynamic postural imbalances in persons with balance related issues with availability of a greater number of channels and more regions of interest to be covered at one given instance.
Keywords: balance; static balance; dynamic balance; cortical activation; neuroimaging; wireless fNIRS